THE INFLUENCE OF CARBIDE DISTRIBUTION ON THE PROPERTIES OF HOT WORK TOOL STEELS - Karaaslan, Ahmet; Akca, Cem (TANGER LTD, 2009)
Essentially, hot work tool steels are expected to resist high temperature in working conditions. Although tempered martensitic structure in hot work tool steels is the most important property that helps achieving high temperature resistance, distribution characteristic of carbides have great effect on this issue as well. Coarser carbides (especially) segregated in grain boundries increase the brittleness of material and result in premature failure of dies. In contrast, homogeneously dispersed finer carbides provides higher toughness and increase in high temperature resistance. In this study, carbide distribution in hot work tool steels have been modified and the results have been examined in terms of microstructural and mechanical investigations. The results have shown that gradual cooling carried out before tempering was a successfull approach to achieve finer carbides (which is ideal) to increase thoughness at elevated temperatures.
Keywords: karbide distribution; hot work tool steels; hot forming; Metallurgy & Metallurgical Engineering